Pre-transplant portal vein thrombosis is an independent risk factor for graft loss due to hepatic artery thrombosis in liver transplant recipients. Issue 3 (March 2016) - Stine, Jonathan G.; Pelletier, Shawn J.; Schmitt, Timothy M.; Porte, Robert J.; Northup, Patrick G.
Abstract: Background: Hepatic artery thrombosis is an uncommon but catastrophic complication following liver transplantation. We hypothesize that recipients with portal vein thrombosis are at increased risk. Methods: Data on all liver transplants in the U.S. during the MELD era through September 2014 were obtained from UNOS. Status one, multivisceral, living donor, re-transplants, pediatric recipients and donation after cardiac death were excluded. Logistic regression models were constructed for hepatic artery thrombosis with resultant graft loss within 90 days of transplantation. Results: 63, 182 recipients underwent transplantation; 662 (1.1%) recipients had early hepatic artery thrombosis; of those, 91 (13.8%) had pre-transplant portal vein thrombosis, versus 7.5% with portal vein thrombosis but no hepatic artery thrombosis (p < 0.0001). Portal vein thrombosis was associated with an increased independent risk of hepatic artery thrombosis (OR 2.17, 95% CI 1.71–2.76, p < 0.001) as was donor risk index (OR 2.02, 95% CI 1.65–2.48, p < 0.001). Heparin use at cross clamp, INR, and male donors were all significantly associated with lower risk. Discussion: Pre-transplant portal vein thrombosis is associated with post-transplant hepatic artery thrombosis independent of other factors. Recipients with portal vein thrombosis might benefit from aggressive coagulation management and careful donor selection. More research is needed to determine causal mechanism.